Tari BalanseMadam dalam Masyarakat Nias di Padang Sumatera Barat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Balanse Madam dance is one of types of folk performing art among Nias community in Padang, West Sumatera Barat. This is danced by a pair persons, with eight dancers as minimal, sixteen dancers ang thirty two dancer as maximal. The dancer must be an adult, without family-ties and has each husband or wive's consent. One of them is chosen as komender, namely someone who will play a role as choreographer for dancing movements and gives signs to move orderly. Balanse Madam dance origines from sincritism beteween Portuguese culture and traditional culture of Nias especially in Seberang Palinggam, and Padang area generally. Today, they still live in that society. The incfluence of Portuguese cultural elements on the dance as an acculturation proses can be seen in the naming and movement forms, performance, music arrangement and performing conditions. Balanse Madam dance which went out of cultural acculturation between traditional native culture and Western culture, is recognized by Niassers in Padang as a cultural product by her supoorting mass. They took it into their tradition, so that it is stated as one of their identities. This dance lives and develops in Minangkabau culture. This performance is always shown as a complement for each ceremony, like the instaling of a clan head, marriage ceremony and helat nageri, as an entertaintment. This study will express about how the position of Balanse Madam dance in Nias community in Padang and it's connection with Minangkabau society as a growing and developing place for the dance. The research is done through multidiciplinary approach, particulary etnochoreology. The writer uses sosiological, anthropological and historical approaches too.